Smooth feedback posture stabilization of a class of mobile robots - Campion, Guy; Bastin, Georges; Mahony, Robert E. (Zielona Góra: Uniwersytet Zielonogórski)
The problem of smooth state feedback posture stabilization of the posture kinematic models of a class of restricted mobility robots is addressed. Three techniques are presented: the first two methods (output linearization and Lyapunov design) ensure the posture stabilization with internal stability of the system while the third one (time-varying smooth state feedback) ensures the stabilization of the full state.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka